PHYTOCHEMICAL SCREENING AND DETERMINATION OF ANTIMICROBIAL, ANTIOXIDANT, AND ANTICANCER ACTIVITY OF ULVA LACTUCA-BASED SILVER NANOPARTICLE - C K BABINI; A REENA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The current study is proposed to evaluate the potential medicinal value of Ulva lactuca an edible green seaweed. The prime objectives of the research were to determine the anti-oxidant, anti-microbial, and anti-cancer properties of the seaweed extracts and green synthesized nanoparticles. Methods: Five different solvent extracts were qualitatively and quantitatively analyzed for phytochemicals. A gas chromatography-mass spectrophotometer (GC-MS) analyzed the metabolite profile of the methanol extract. In-vitro anti-oxidant activity is determined by 1-diphenyl 2-picrylhydrazyl (DPPH) and ABT assay. The Resazurin method tested the anti-microbial activity against two uropathogenic bacteria and one fungal pathogen. HeLa cell line was employed to investigate the anti-cancer potential of the seaweed conjugated nanoparticle. Results: Qualitative analysis revealed the presence of Alkaloids, Phenol, flavonoids, tannins, steroids, carbohydrates, glycosides, amino acids, and proteins. The metabolite profiling of methanol extract was identified by GC-MS analysis. Quantitative estimation exposed total flavonoid content of 2.56±0.30 mg quercetin equivalent/g, total phenolic content −3.66±0.15 mg gallic acid equivalents/g, Tannic acid equivalent – total tannin content (TTC) of 2.90±0.61 mg/g and 3.40±0.30 mg/dL of steroids. EAE, ME, and HE recorded the following IC50 for DPPH −871 μg/mL, 432.264 μg/mL, and 432.273 μg/mL, respectively. In ABTs, AE, ME, and EAE showed the highest activity at IC50 values of 39.090 μg/mL, 104.43 μg/mL, and 252.491 μg/ mL. MIC of Ulva NP against Escherichia coli −250 μg/mL, Candida albicans −500 μg/mL, and Acinetobacter baumannii −1000 μg/mL was depicted. The cytotoxicity nature of UAgNPs is observed in HeLa cell lines. The screening results reveal that the edible green seaweed U. lactuca can be further studied and extended as a potential source of components in controlling Urinary tract infection (UTI) and a drug of choice for cervical cancer. Conclusion: The current study highlights the antimicrobial, antioxidant, and anticancer properties of green seaweed U. lactuca, a potential source of pharmaceutical application.